2022
DOI: 10.1371/journal.pntd.0010083
|View full text |Cite
|
Sign up to set email alerts
|

Community trust of government and non-governmental organizations during the 2014-16 Ebola epidemic in Liberia

Abstract: The West African Ebola Virus Disease epidemic of 2014-16 cost more than 11,000 lives. Interventions targeting key behaviors to curb transmission, such as safe funeral practices and reporting and isolating the ill, were initially unsuccessful in a climate of fear, mistrust, and denial. Building trust was eventually recognized as essential to epidemic response and prioritized, and trust was seen to improve toward the end of the epidemic as incidence fell. However, little is understood about how and why trust cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
2
6
0
Order By: Relevance
“…Higher compliance rates and reduced death rates may be linked to trust [29]. However, during the Ebola pandemic in Liberia in 2018, a study found that community trust in non-governmental organizations (NGOs) was stronger than in government [30]. People seek information from various resources to update their knowledge and become more prepared in the face of COVID-19 [31].…”
Section: Discussionmentioning
confidence: 99%
“…Higher compliance rates and reduced death rates may be linked to trust [29]. However, during the Ebola pandemic in Liberia in 2018, a study found that community trust in non-governmental organizations (NGOs) was stronger than in government [30]. People seek information from various resources to update their knowledge and become more prepared in the face of COVID-19 [31].…”
Section: Discussionmentioning
confidence: 99%
“…Without common recognition of an epidemic, perceived threat is non-existent, and behavior change is not viewed as important or warranted [ 15 ]. Widespread denial reflects deep-seated distrust of the government held by many Liberians [ 12 , 13 ] and represents an unsolved problem that is likely to re-emerge during future public health crises. This study provides insight into drivers of distrust and denial that continue to undermine community readiness for future epidemics in Liberia.…”
Section: Discussionmentioning
confidence: 99%
“…We purposively selected three Liberian locations (as previously described [ 13 ]) for their distinct experiences during the Ebola epidemic: Duazon in Margibi County with a high level of exposure to Ebola response activities and low incidence of Ebola; Careysburg in Montserrado County with low exposure to response activities and low Ebola incidence; and Tubmanburg in Bomi County with high exposure to response activities and high Ebola incidence. In each of these study sites, we partnered with local leadership to first conduct pre-mobilization meetings to notify the community.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations